1994
DOI: 10.1002/hlca.19940770121
|View full text |Cite
|
Sign up to set email alerts
|

Short Optimally Capped Duplex DNA as Conformationally Restricted Analogue of B‐DNA

Abstract: We describe the synthesis of short double-stranded DNA fragments (see 4 and 13) which are capped on both ends by an optimally designed linker molecule. The new structures are stable with respect to hybrid dissociation and should have implications in physical studies involving double-stranded DNA as well as in the antisense area for the specific modulation of gene expressions.1. Introduction. -Physical studies on DNA and DNA complexes with proteins/peptides or small molecules are mainly performed on oligonucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Alternatively, dumbbells can be made chemically by phosphorylating during solidphase synthesis and ligating using either 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide hydrochloride (EDC) 87 or CNBr. 88 alkyl tethers of varying lengths (3-to 5-atoms) are positioned at the N 6 of adenosine (26), 105 the N 2 of guanosine (27), 106 or the N 4 of cytosine (28). 107,108 The resultant disulfides occupy the grooves of the helix (Figure 7).…”
Section: B Conformationally Restraining Minimal Oligonucleotidesmentioning
confidence: 99%
“…Alternatively, dumbbells can be made chemically by phosphorylating during solidphase synthesis and ligating using either 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide hydrochloride (EDC) 87 or CNBr. 88 alkyl tethers of varying lengths (3-to 5-atoms) are positioned at the N 6 of adenosine (26), 105 the N 2 of guanosine (27), 106 or the N 4 of cytosine (28). 107,108 The resultant disulfides occupy the grooves of the helix (Figure 7).…”
Section: B Conformationally Restraining Minimal Oligonucleotidesmentioning
confidence: 99%
“…Other approaches involve the incorporation of a covalently-closed base pair (bp) at one end of the duplex (3,4) or cross-linking steps after the oligonucleotide synthesis (5-10). More recently several groups have proposed introducing synthetic linkers as phosphoramidite building blocks during DNA synthesis, with linkers of hexaethylene glycol (11), triethylene glycol (12), 1,3-dihydroxy-propane or 1,9-dihydroxynonane (12), alkyl chains containing the terephthalamide group (13) or two 1,3-dipropanol units connected by a phosphate group (14). This technique was also used to synthesize DNA dumbbells with two synthetic linkers at each end of a duplex, with the linkers being 1,3-dihydroxy-dodecane (15) or two 1,3-dihydroxy-propane moieties connected by a phosphate group (14).…”
Section: Introductionmentioning
confidence: 99%
“…More recently several groups have proposed introducing synthetic linkers as phosphoramidite building blocks during DNA synthesis, with linkers of hexaethylene glycol (11), triethylene glycol (12), 1,3-dihydroxy-propane or 1,9-dihydroxynonane (12), alkyl chains containing the terephthalamide group (13) or two 1,3-dipropanol units connected by a phosphate group (14). This technique was also used to synthesize DNA dumbbells with two synthetic linkers at each end of a duplex, with the linkers being 1,3-dihydroxy-dodecane (15) or two 1,3-dihydroxy-propane moieties connected by a phosphate group (14). For the hexaethylene glycol linker it has been qualitatively demonstrated that no large structural perturbations are introduced since the lac repressor and its N-terminal headpiece bind with similar characteristics to a mini-operator linked by hexaethylene glycol or to the operator fragment containing no linker (16).…”
Section: Introductionmentioning
confidence: 99%
“…This was first performed using 2 x C3 units to create 'sausage DNA' which showed a Tm 40 °C higher than the uncapped version. 33 HEG has been used to link two T-rich sequences into an elongated cyclic structure which then bound a third strand, raising Tm of the triplex by 16 °C. HEG also shows benefits for linear, folded, triplex structures, giving an 18 °C increase in Tm.…”
Section: Non-nucleosidic Insertions In Nucleic Acidsmentioning
confidence: 99%